2002
DOI: 10.1093/genetics/162.4.1885
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of an Elite Rice Hybrid Revealed That Heterozygotes Are Not Always Advantageous for Performance

Abstract: We introduced an experimental design that produced an “immortalized F2” population allowing for complete dissection of genetic components underlying quantitative traits. Data for yield and three component traits of the immortalized F2 were collected from replicated field trials over 2 years. Using 231 marker loci, we resolved the genetic effects into individual components and assessed relative performance of all the genotypes at both single- and two-locus levels. Single-locus analysis detected 40 QTL for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(36 citation statements)
references
References 21 publications
2
30
0
4
Order By: Relevance
“…The non-significant correlation recorded between SSR-based GD, hybrid performance, heterosis (mid or better parent) and SCA effects for all the studied traits could be a result of using a relatively small number of markers. Analogous findings were reported by Xiao et al [ 26 ], Hua et al [ 35 ], Gramaje et al [ 22 ], and Zhang et al [ 88 ]. However, Xangsayasane et al [ 31 ] and Singh et al [ 33 ] reported a significant association between GD, heterosis and hybrid performance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The non-significant correlation recorded between SSR-based GD, hybrid performance, heterosis (mid or better parent) and SCA effects for all the studied traits could be a result of using a relatively small number of markers. Analogous findings were reported by Xiao et al [ 26 ], Hua et al [ 35 ], Gramaje et al [ 22 ], and Zhang et al [ 88 ]. However, Xangsayasane et al [ 31 ] and Singh et al [ 33 ] reported a significant association between GD, heterosis and hybrid performance.…”
Section: Discussionsupporting
confidence: 88%
“…Microsatellites or simple sequence repeats (SSR) are valuable markers due to their co-dominant transmission, multi-allelic nature, relative abundance, genome coverage, informativeness, and low DNA requirement [ 30 ]. Numerous published reports have revealed a significant relationship between GD-based molecular markers with F 1 hybrid performance and heterosis [ 31 , 32 , 33 ], although other studies have detected no significant correlation [ 22 , 26 , 34 , 35 ]. We hypothesized that crossing diverse exotic and local rice genotypes with different levels of tolerance to water deficit would provide promising high-yielding and tolerant F 1 hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…An IMF2 (immortalized F 2 ) population of rice with n = 278 hybrids was used as an example for illustration [ 54 ]. The trait is the 1000-grain weight (KGW).…”
Section: Resultsmentioning
confidence: 99%
“…A normalized kinship matrix has a property of tr( K ) = n , i.e., the trace of K equals the sample size. The data were originally published by Hua et al [ 54 ] and later by Xu et al [ 55 ]. We illustrated the analysis of a single marker (Bin725) as an example.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, two QTLs were overlapped on chromosome 6 in the same marker interval RM528-RM20632 in both the repeated experiments. Li et al and Hua et al characterized qGP3-1 and qGP-6, respectively, associated with grain number per panicle [32,33]. It is also reported that the GA biosynthesis gene (OsGA20ox1) is located in qGP3 for the number of grains per panicle [34].…”
Section: Discussionmentioning
confidence: 97%